Use financial aid strategically, communicate effectively for enrollment success. Issue 4 (10th June 2022) - Hope, Joan
Abstract : The University of South Florida welcomed its largest freshman class ever in fall 2021, and the institution has seen increases in net tuition revenue since 2013. Those are among the successes Billie Jo Hamilton, M.B.A., has overseen as Associate Vice President for Enrollment Planning and Management.